REGIONAL DIVERSIFICATION IN FINANCING RURAL AREA DEVELOPMENT IN POLAND IN THE YEARS 2007-2013 - Jarosław Gołębiewski; Olga Podlińska (Polityki Europejskie, Finanse i Marketing)
The article presents diversified use of EU funds on rural areas in Poland by region in the years 2007-2013. The objective of the article is to present and assess diversification in financing development of Polish rural areas within the framework of the Rural Development Program for the years 2007-2013. The majority of funds has been provided for implementing the activities from the Axis 1, however, the activities from the Axis 2 have been observed as the most popular among beneficiaries. The most resources from RDP 2007-2013 have been provided for the following provinces: mazowieckie, wielkopolskie and lubelskie, whereas the lowest level of resources has been provided for such provinces as: opolskie, lubuskie and śląskie.